E-TOURISM: CONCEPT AND EVOLUTION - Condratov, Iulian (Ecoforum Journal, 2013)
Tourism has closely been connected to progress of ICTs for over 25 years. Nowadays, the Internet and ICTs are relevant on all operative, structural, strategic and marketing levels to facilitate global interaction among suppliers, intermediaries and consumers around the world. This paper provides a review for the key aspects of ICT that influenced and influence the tourism sector activity. Two themes were identified as forming the basis of researching in the e-tourism domain: the technological progress and the impact on the touristic market. The paper also presents future developments in eTourism that will influence the tourism industry structure.